In which group of children and adolescents should a family doctor look for metabolic syndrome? - Banaś, Izabela Maria; Lewek, Paweł Krzysztof; Kardas, Przemysław (Family Medicine & Primary Care Review, 2016)
Background. The asymptomatic course, early genesis, multifactorial onset, and the lack of a single definition of metabolic syndrome in children and adolescents make it difficult to assess its prevalence. Metabolic syndrome developed in childhood increases cardiovascular risk in adulthood. Objectives. The evaluation of the prevalence of metabolic syndrome based on age, sex, weight and abdominal obesity in a population of children and adolescents in a family doctor’s practice. Material and methods. The study group comprised 325 children and adolescents (177♀, 148♂) aged 7, 13 and 16 years. Anthropometric measurements (height, weight, waist circumference) were made, along with the determination of blood pressure, fasting glucose and lipid levels. Overweight states and obesity were assessed according to the IOTF criteria. Abdominal obesity and hypertension were evaluated using growth charts appropriate for the age, gender and height of the children of Lodz. Metabolic syndrome was diagnosed based on the NCEP/AT P III criteria. Results . Metabolic syndrome was diagnosed in 6.5% of the subjects. In children aged 13 and 16 years – 7.6% (p > 0.05 vs. 7 years), aged 7 years – 3.9% (p > 0.05 vs. 13, 16 years), boys (8.8%; p > 0.05), girls (4.5%; p > 0.05). Among children with excessive body weight, metabolic syndrome was observed in every fourth child (25.4%), more often in those with obesity (44.1%) than with abdominal obesity (32%) and those who were overweight (19.2%), respectively (p < 0.001 vs. metabolic syndrome). The number of components of metabolic syndrome elevated with increasing body weight (p < 0.001). Abdominal obesity was observed in 17.5% of the subjects. Children with abdominal obesity had higher levels of triglycerides (p < 0.05) and lower HDL cholesterol (p 110 mg/dl in 85 (26.1%) and excessive body weight in 71 subjects (21.8%). Conclusions . The presence of metabolic syndrome correlated with overweight state, obesity and abdominal obesity in the group of children and adolescents. The evaluation of cardiovascular risk performed in obese children by a family doctor allows for the early implementation of prevention.